Основы инициативы евразийской интеграции сельского хозяйства - Зиядин Саябек; КабашеваНаталья (Вопросы государственного и муниципального управления, 2018)
This article discusses the basics of the integration of Eurasia’s agricultural sector, based on the integration process between the European Union (EU) and Asian countries. The EU’s agricultural integration has to be regarded as an innovative, large-scale project. The transformation of the EU’s agricultural market has proven to be a complex agricultural integration that combines multiple ideological, financial, and political interests. Throughout the period of the EU’s agricultural integration, its financial instruments and structured management were stable and, consequently, the integration was effective. However, the development stages of the ecological agriculture projects (EAP) study showed that the formation of a competitive EU agricultural market had some disadvantages. The complexity of the development of the agricultural market in Asian countries, including Kazakhstan and China, results from the fact that, unlike Europe, the Asian countries are at significantly different levels of development with respect to their economic, cultural, and political systems.